Kinematic Flow Parameters During Liquid Movement in Pressurized Water Pipelines - Dalabaev , Umriddin; Arifjanov, Aybek; Apakhodjaeva, Tursinoy; Abduraimova, Dilbar; Xoshimov, Sardor (International Journal of Psychosocial Rehabilitation, 2020)
In solving a number of practical problems associated with the flow of fluid in pipelines of various sections with steady and unsteady fluid motion, it becomes necessary to determine the kinematic parameters of the flow. In this paper, we consider solving a number of problems by the method of movable nodes. Using specific examples, the capabilities of this method are evaluated in comparison with other methods. The application of the method of moving nodes to the problems of flow in a flat pipe, flow in an ellipsoidal pipe, and flow in a rectangular pipe is considered. A comparison of the exact and approximate solutions obtained on the basis of the method of moving nodes in the cross section x  0 at   1 is given. Comparison shows that the calculation by the above method gives a more accurate result. The maximum absolute difference between the exact and approximate solutions is 0.024. The problem of the transient flow of a viscous fluid between parallel walls is considered. The results show that partial approximations give better results compared to full approximations. Moreover, the best approximation in comparison with others is given at small t.